The Dissolution of the Powder Trust - Stevens, William S. (Quarterly Journal of Economics, 1912)
The Dissolution of the Powder Trust Get access William S. Stevens William S. Stevens Columbia University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 27, Issue 1, November 1912, Pages 202–207, https://doi.org/10.2307/1882675 Published: 01 November 1912